PENGELOLAAN KESAN DALAM KOMUNIKASI PERTEMANAN DI INSTAGRAM (Studi Kualitatif dengan Pendekatan Dramaturgi Pada Mahasiswa FISIP UPN Veteran Jakarta) - Tasya Nabilah Afifah, (2021)
Nowadays, social media is used to give and receive information, share photos or videos, communicate with others and make friends. The existence of Instagram, raises a phenomenon, namely Insta-Lie, where Instagram users build "fake" characters in order to get recognition on social media. Users make an impressions on Instagram in order to get an impression from friends on Instagram. The communication between the virtual world and the real world are also different. This will affect self image on Instagram. Based on this, the researcher has made research questions, that are (1) how do informants view self-image in public ?, (2) how do informants manage impressions on Instagram (front stage) ?, (3) what is the back stage of Instagram users? The research questions were answered through interviews, observations, and documentation that the researchers had done. This study uses a qualitative research method, with Erving Goffman's dramaturgy approach. The informants in this research were seven people with different professions. The result of the research findings are (1) The informants display self-image on Instagram in relation to personality, physical appearance, and lifestyle (2) Self-image on Instagram is influenced by internal and external factors, (3) The informants perform impression management by posting consistent content using settings, appearance, and manner, (4) There was an incident while appearing on the front stage and then resolved with an action, (5) Features of Instagram that are used by informants to build images and communicating with friends on Instagram are feeds and Insta stories, (6) Responses from friends on Instagram can influence informants, (7) There are differences that are displayed by the informants whileon the front stage and on the back stage that are personal characteristics, communication, and preparation to appear on the front stage.